2018
DOI: 10.1177/1087054718815588
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of Sex Differences on Delay of Gratification and Temporal Discounting Tasks in ADHD and Typically Developing Samples

Abstract: Objective: To examine whether males and females with ADHD differ in their preferences for delayed rewards, since there is some evidence that suggests a sex difference with typically developing (TD) samples. Method: We used meta-analyses to examine sex differences on delay of gratification and temporal discounting tasks in both TD and ADHD samples. We identified 28 papers with 52 effect sizes for children and adults, and calculated the average effect size for sex comparisons within TD and ADHD samples. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 133 publications
(189 reference statements)
3
17
0
1
Order By: Relevance
“…However, the pattern of results (described thus far) should factor in gender.. Mirroring previous research, the present findings suggest that men and women with ADHD experience different challenges ( Doidge, 2017 ; Vogley, 2019 ). For example, previous research has found that women with ADHD may have more difficulties with delayed gratification than men with ADHD, and that this can at least partly explain women with ADHD’s overall greater impairment ( Doidge, 2017 ) Women with ADHD are also at enhanced risk for relationship problems ( Tureau, 2004 ). Paradoxically, however, women with ADHD have higher educational attainment than men with ADHD ( Velki & Vrdoljak, 2019 ).…”
Section: Discussionsupporting
confidence: 50%
“…However, the pattern of results (described thus far) should factor in gender.. Mirroring previous research, the present findings suggest that men and women with ADHD experience different challenges ( Doidge, 2017 ; Vogley, 2019 ). For example, previous research has found that women with ADHD may have more difficulties with delayed gratification than men with ADHD, and that this can at least partly explain women with ADHD’s overall greater impairment ( Doidge, 2017 ) Women with ADHD are also at enhanced risk for relationship problems ( Tureau, 2004 ). Paradoxically, however, women with ADHD have higher educational attainment than men with ADHD ( Velki & Vrdoljak, 2019 ).…”
Section: Discussionsupporting
confidence: 50%
“…This sample promoted homogeneity for consideration of underlying mechanisms; however, generalizability of findings to males remains to be established. Effects of gender on hypothetical intertemporal choice have been mixed [126][127][128], with findings thought to be due in part to hormonal influences on neurobiological mechanisms of reward [129]. Such factors could differentially affect experiential intertemporal choices and may need to be controlled for in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, DRD might be linked to parent marital status through the association of parent marital status and socioeconomic status (Karney, 2021) or through the association of marriage with religiosity (Pew Research Center, 2014), which has been linked to lower rates of DRD (Weatherly & Plumm, 2012). A recent meta-analysis did not find sex differences in DRD among typically developing children, though it did find higher DRD in females with attention-deficit/ hyperactivity disorder than males with the disorder (Doidge et al, 2021). However, in the present study, being male was a predictor of higher DRD.…”
Section: Discussionmentioning
confidence: 99%